The Effectiveness of Positive Coping Program on Reduction of Addiction Potential in Students - Fatemeh Nematollahi; Mahmoud Golzari; Jamal Shams (Drug Control Headquarters, Research and Education Office, 2010)
Objective: This study aimed to study the effectiveness of positive coping program on reduction of addiction potential in dormitory girl students. Method: The research method was semi experimental method namely: pre test-post test with witness group. In selection of sample, first addiction potential scale administered among 160 dormitory girl students, and 20 of them who were scored higher than cutoff score on addiction potential scale selected and divided to two experimental and witness groups. Experimental group received 10 sessions training which each session was 90 minutes. Positive coping program was based on three components of Bob Murray's theory namely: social relationships, goal setting and spirituality. After finishing of training Post test were administered in both experimental and witness groups. Results: The results showed positive coping training was significantly reduced students' addiction potential. Conclusion: The training of positive coping can be affect on reduction of girl students' addiction potential.